An assessment of Blaine's air permeability method to predict the filtration properties of iron ore concentrates. (1st January 2021) - Safonov, Dmitry; Kinnarinen, Teemu; Häkkinen, Antti
Highlights: Mixtures preparation approach is useful to study materials with different particle size distribution. Filtration characteristics correlates with the materials specific surface area. Blaine meter can give information about filtration cake porosity and resistance. Suspension filterability can be predicted using the small quantity of test sample. Blaine meter data can be used to predict the filtration properties of iron-ore suspensions; Abstract: The design of new filtration equipment and its further insertion into full-scale industrial use requires to perform a filtration-testing project. Usually, a complete, standard project depends on the transportation of a significant amount of test materials to a remote laboratory or moving and adjusting a pilot-scale filter directly in the plant area. These transportation expenses can affect the cost of the entire testing project dramatically. Additionally, maturing mining technology and the gradual depletion of mineral deposits have led to the continually growing costs of available sample materials. Suppliers of filtration equipment are actively searching for new testing methodologies to be able to design full-scale equipment with a minimum testing time, cost, and sample size. This paper investigates the applicability of simple particle size testing equipment – a Blaine's air permeability apparatus – for the estimation of the filtration behavior of iron ore concentrates from samples as small as just a few grams. The results of experiments performed with mixtures of iron concentrates showed that the testing equipment, along with proposed methodologies with regression equations and empirically determined parameters, could be applicable for rough and express estimation of average specific cake resistance.